Impact of ASEAN rice policy on intra-ASEAN rice trade - Dordkeshan, Mohammad Javad (2016)
The Association of Southeast Asian Nations (ASEAN) member countries have implemented various plans to achieve the integrated economic growth, political and cultural development in the region. In order to realize their economic goal, the ASEAN Economic Community (AEC) has been implemented by member countries through the ASEAN Free Trade Area (AFTA) agreement to experience free market situation. Due to political and dietary importance of rice, historically, the ASEAN member governments have intervened in the rice sector using different policy instruments. However, these interventionist policies may not be sustainable in the long-term as they incur a high budgetary burden to the government. On the other hand, globalization asked for a greater market access with gradual elimination of all different types of market distortions and trade barriers. In this study, five selected countries which are Malaysia, Indonesia, the Philippines, Thailand, and Vietnam have signed several international trade organizations such as World Trade Organization (WTO), Asian-Pacific Cooperation (APEC) and ASEAN Free Trade Area (AFTA) to boost free trade market structure. Therefore, they are duty bound to eliminate governments’ interventions gradually. The main focus of this study was on quantitative restriction policies which are considered as more effective market distortion than other governments’ interventions. Therefore, the effect of changes in the minimum export price policy for Thailand and Vietnam as well as import quota in Malaysia were examined in this study. Minimum Export Price (MEP) policy is a method of controlling the volume of export when the international rice market introduces more competitive price. Thailand and Vietnam implemented MEP policy after the food crisis of 2007-2008 to control their rice export price that might change the rice trade flow within ASEAN region. In addition, Import quota is a way of protecting domestic rice production by giving permission to only a certain quantity of rice to be imported. In Malaysia, the rice import quota is constant at 700,000 tons per year which was started in 2010 by the Malaysian Ministry of Agriculture. The general objective of this study was to investigate the impact of ASEAN rice policy on Intra-ASEAN rice trade in the five selected ASEAN countries with those following specific objectives of developing a system dynamics model for ASEAN rice sector, simulating the impact of ASEAN rice policy on intra-ASEAN rice sector namely changes in Minimum Export Price in Vietnam and Thailand, and the rice import quota in Malaysia. System Dynamics (SD) methodology was used to understand the complexity of rice sector in five selected ASEAN member countries and forecast the future situation of rice industry in this region until 2025. First, causal loops diagram were developed based on the literature explanation of relationships between the variables in the rice industry, then secondly, stock and flow diagrams were built based on the casual loop diagrams to run computer simulation and forecast using Vensim software. Simulations were run based on five scenarios which were designed based on comparison between Thailand and Vietnam rice export price with international price, considering the implementation of MEP policy in Thailand and Vietnam along with eliminating import quota mainly in Malaysia. Simulation results indicated that Vietnam will dominate the rice market in the region up to 85-90% of total Indonesia, Malaysia and the Philippines rice import in 2025. However, Thailand might loss up to less than 10% of its trade partners in the region at the same period of time. Hence, ASEAN rice importer countries need to manage reliable sources of rice supply probably from outside the region in case of the shortage in their own local market and at the time of food crisis due to food security concern.